Saving liberal internationalism from a liberal world order in crisis - Lovec, Marko (Teorija in praksa, 2019)
The paper explores the apparent crisis of the liberal world order, arguing that liberal internationalism is today still more part of the solution. In particular, it argues that political disintegration tendencies reflect the declining costs of independence and ever smaller role of political power in general; that democratic opposition to trade should be seen in the context of increasingly mobile "winners" and immobile "losers" with populist nationalism being the only way in which territorialised systems of representation can respond; and that the centrifugal tendencies observed in regions are a sign of competitive and multilateral rather than a conflictive and regiocentric world.
Keywords: Globalizacija; Globalization; Liberalism; Liberalizem; New world order; Novi svetovni red; Populism; Populizem; Regionalism; Regionalizacija